Kinematics analysis of selected rhytmic gymnastic leaps - Cicchella, A. (Journal of Human Sport & Exercise, 2009)
Very few studies exist on biomechanics of rhythmic gymnastic. Four leaps of an experienced high level (national competition) rhythmic gymnast athlete (16yo, 175 cm height, 50 kg weight) were analyzed in order to provide firsts descriptive data of these movements, to compare different behaviour in similar jumps and to study its variability. The subject performed 10 trials for each of the four movements, for a total of 40 trials, barefoot on a laboratory with a rubber floor. A total of 40 trials were analyzed for grand jetè, kosak jump, kosak jump with half turn, turn scissor jump. The four movements were split into four phases: last stride length (LS), distance between toe off and heel contact of last stride, knee loading angle previous to jump (KL), defined as maximum loading angle at the knee, push time (PD), defined as the time of push off, and flight time (FT). The lower variability, was observed in flight times of all four leaps (2.24-2,92 %), suggesting a strategy to maintain constant this variable among the 10 trials, despite the kind of jump being performed. Last stride lengths, knee loading angles previous to jump, push times and flight times were computed by means of a Vicon 460 motion analysis system. The lowest variability was shown by flight times, and the highest by last stride lengths. All jumps showed similar flight time, despite the different movements being performed during the flight phase. All variables shows to be normally distributed except last stride length of the grand jete (r=0,753; p=0,009) and flight time of cosak jump with half turn (r=0,749; p=0,008). Correlations between all leaps kinematics variables show the influence of push times (r= -0,685; p=0,000) and of the last stride length (r=0,533; p=0,001) on flight times. Flight times were kept constant in all jumps, despite the high (3,90-10,59%) variability in push time and in last stride length.